2003
DOI: 10.1038/sj.cgt.7700643
|View full text |Cite
|
Sign up to set email alerts
|

Non-small lung cancer cells are prime targets for p53 gene transfer mediated by a recombinant adeno-associated virus type-2 vector

Abstract: In this study, we elucidated the potential of recombinant adeno-associated virus type-2 (rAAV-2) vectors for lung cancer gene therapy. Cell lines of the three major histological subtypes of non-small cell lung cancer (NSCLC) were highly susceptible for rAAV-2 showing transduction rates between 63.4 and 98.9%. In contrast, cell lines of small cell carcinomas were resistant to rAAV-2 infection. For restoration of p53 function in p53 deficient NSCLC, a rAAV-2 vector was constructed containing wt p53 cDNA. Followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Thus, we hypothesize that a low dose of GA can enhance the ability of I 131 to regulate Bcl-2 and Bax expression, which may promote apoptosis in A549/DDP cells. Other previous studies of lung cancer have found that wild-type P53 can promote tumor cell apoptosis (46,47), increasing the chemosensitivity of tumor cells (48,49). However, mutant P53 can promote chemotherapeutic tolerance in tumor cells via several factors, such as decreased pro-apoptotic capacity, increased DNA repair function (50,51) and upregulated P-gP expression (9,52).…”
mentioning
confidence: 99%
“…Thus, we hypothesize that a low dose of GA can enhance the ability of I 131 to regulate Bcl-2 and Bax expression, which may promote apoptosis in A549/DDP cells. Other previous studies of lung cancer have found that wild-type P53 can promote tumor cell apoptosis (46,47), increasing the chemosensitivity of tumor cells (48,49). However, mutant P53 can promote chemotherapeutic tolerance in tumor cells via several factors, such as decreased pro-apoptotic capacity, increased DNA repair function (50,51) and upregulated P-gP expression (9,52).…”
mentioning
confidence: 99%
“…17 For p53 gene transfer, an rAAV-2 vector was used as we previously demonstrated that NSCLC cells are highly susceptible for rAAV-2. 20,32 The results of previous clinical trials using p53 gene replacement therapy in combination with chemotherapy were disappointing. Although the approach was safe and restoration of p53 was successful, the clinical benefit for the patient was marginal.…”
Section: Discussionmentioning
confidence: 99%
“…20 Briefly, 1 Â 10 5 cells were plated in 24-well plates and incubated with an IC 50 of rAAV-p53 and bortezomib alone and in combination with bortezomib for 24 h. As primary antibodies, a monoclonal mouse antihuman p53 antibody (Clone DO-7, Dako Cytomation, Hamburg, Germany; dilution 1:500) and a monoclonal mouse antirabbit glyceraldehyde-3-phosphate dehydrogenase (GAPDH) antibody (Clone 6C5, Acris Antibodies, Hiddenhausen, Germany; dilution 1:25000) were used. The primary antibodies were detected with a peroxidasecoupled rabbit antimouse secondary antibody (P0161, Dako Cytomation, Hamburg, Germany; dilution 1:1000).…”
Section: Western Blot Analysismentioning
confidence: 99%
See 2 more Smart Citations